Rowing in Los Angeles: performance considerations for the change to 1500 m at the 2028 olympic games - Astridge, D. J.; Peeling, P.; Goods, P. S. R.; Girard, O.; Hewlett, J.; Rice, A. J.; Binnie, M. J. (International Journal of Sports Physiology and Performance, 2023)
Background: World Rowing`s decision to support the proposed change from a 2000-m to a 1500-m regatta course at the 2028 Olympic Games in Los Angeles is anticipated to have important implications for athlete preparation and race execution during the 2024-2028 quadrennium.